2023
DOI: 10.1096/fj.202300261rr
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomics unravels altered phenylalanine levels in piglets receiving total parenteral nutrition

Abstract: Parenteral nutrition, received by many patients with intestinal failure, can induce hepatobiliary complications, which is termed as parenteral nutrition-associated liver disease (PNALD). The spectrum of PNALD ranges from cholestasis and steatosis to fibrosis and cirrhosis. Although many factors contribute to the pathogenesis of PNALD, the underlying mechanisms remain unclear. In this study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…After L. johnsonii treatment, liver steatosis was attenuated as a result of decreased fatty acid synthesis and increased fatty acid oxidation. We previously showed that the expression of hepatic Cpt1α, an enzyme involved in fatty acid oxidation, was significantly suppressed in both piglet and rat models of PNALD [23]. Here, we found that L. johnsonii promoted the expression of Cpt1α, while the underlying mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…After L. johnsonii treatment, liver steatosis was attenuated as a result of decreased fatty acid synthesis and increased fatty acid oxidation. We previously showed that the expression of hepatic Cpt1α, an enzyme involved in fatty acid oxidation, was significantly suppressed in both piglet and rat models of PNALD [23]. Here, we found that L. johnsonii promoted the expression of Cpt1α, while the underlying mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 78%
“…In our previous studies, we established that TPN infusion for 7 days led to the manifestation of liver steatosis and perturbation in bile acid metabolism in rats [5,13,23]. We first evaluated body weight (Supplementary Figure S1A) and the percentage of liver/body weight (Supplementary Figure S1B).…”
Section: Johnsonii Treatment Alleviates Hepatic Steatosis In Tpn-fed ...mentioning
confidence: 99%
“…Among the described amino acids, phenylalanine has been revealed to be the most efficient [ 81 ]. L-arginine reduces oxidative stress and L-Glutamine diminishes inactive energy expenditure [ 82 ]. Niihara [ 83 ] reported a phase 3 trial demonstrating efficacy in reducing acute complications of SCD, leading the FDA to approve pharmaceutical-grade L-glutamine (Endari, Emmaus Medical) as a prescription medication for adults and children aged 5 and above.…”
Section: Functional Food Exploited In Scd Managementmentioning
confidence: 99%